2012
DOI: 10.1177/1477370812454369
|View full text |Cite
|
Sign up to set email alerts
|

Self-protective behaviours against crime in urban settings: An empirical approach to vulnerability and victimization models

Abstract: Previous research on the relationships between age, sex, ethnic group or previous victimization experience and fear of crime is controversial, as inconsistent results have been obtained, many of them attributable to a lack of methodological and conceptual consensus. We propose the study of self-protective behaviours motivated by fear of crime as a useful alternative that pays attention to the consequences of fear for urban quality of life. A survey with a representative sample of residents in a major city in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
11
0
8
Order By: Relevance
“…Likewise, according to the report made by the Government of the State of Morelos d , in recent years, most frequent crimes are fundamentally violent and predominantly affect men who are both victims and perpetrators. In a study conducted by San-Juan et al 17 , it was found that women were victims more often than men. However, our study shows that the percentage of victimized men and women is very similar (12.9% and 13.2%, respectively).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Likewise, according to the report made by the Government of the State of Morelos d , in recent years, most frequent crimes are fundamentally violent and predominantly affect men who are both victims and perpetrators. In a study conducted by San-Juan et al 17 , it was found that women were victims more often than men. However, our study shows that the percentage of victimized men and women is very similar (12.9% and 13.2%, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly to what happens with restrictions of everyday activities, men, especially those who were victims of crime, adopt more protective measures than women. As noted by San-Juan et al 17 , the family protection is, still, a responsibility assigned mainly to men. In this sense, being a victim of crime can involve a failure in the task of protecting yourself and your family 20 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Security is also provided privately in many public areas, so that safety has become less of a public right (Zedner, 2003), and in some cases access to security is becoming a kind of club good, brokered by the ability to afford entry to bubbles of safety in predictable and secured spaces (Hope, 2000). Despite public space appearing to be an open and shared asset, our social backgrounds offer particular vantage points from which avoidance behaviours (of particular neighbourhoods) and security measures are implemented (San-Juan, Vozmediano, & Vergara, 2012).…”
Section: Included Excluded and Rejected Spacesmentioning
confidence: 99%
“…Thus, the role of the victim in this process is essential, because without information from the population it is difficult to develop effective actions to control crime. In this sense, Carneiro [9] comments that the information provided by the victims of the crime is relevant to the crime-fighting policies. It complements saying that the crimes that cause a greater sense of insecurity are those related to homicide, assault, rape, and theft.…”
Section: Crime and The Fear Of Crimementioning
confidence: 99%